Analysis Of The Quality Of Services and Physical Facilities Of The Hospital On Word Of Mouth With Patient Experience As An Intervening Variable At Mekar Sari Hospital - Dani Sagitha; Natsir Nugroho; Lily Widjaja (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
This research is aimed at analyzing the influence of service quality and physical facilities on WoM (Word of Mouth) with Patient Experience as an intervening variable at Mekar Sari Hospital. The research method used in this research is a correlational quantitative research type with a cross-sectional research design approach by looking at the influence of service quality and physical facilities on WoM with satisfaction as an intervening variable.The sampling technique used purposive sampling, namely a sampling technique using the criteria of internal medicine inpatients at Mekar Sari Hospital. The research sample involved 110 respondents. Path analysis is used as a WoM model analysis tool with patient experience as an intervening variable.The results of this study found a joint positive influence of service quality and physical facilities on WoM with patient experience as an intervening variable. The quality of service and physical facilities have a positive influence on both patient experience and WoM.